Genetic variability of Italian Heavy Draught Horse - Fabio Maretto (Italian Journal of Animal Science, 2010)
This study aimed to analyze the genetic variability of the Italian Heavy Draught Horse (IHDH) breed using a panel of 23 microsatellite markers. We also compared the population structure of the IHDH to other two unrelated breeds (Italian Haflinger, IH and Quarter Horse, QH). The IHDH showed a genetic variability comparable with other European heavy draught horse breeds and with the IH and QH breeds analyzed. Clustering analyses using a posterior Bayesian approach clearly differentiated the three breeds; it also showed a fragmentation of the IHDH in three subpopulations that need to be further investigated. These findings are an indicator of the present situation of the IHDH and will contribute to the conservation and implementation of the selection programme for this breed.